Study of a model of a satellite structure that meets the necessary criteria for stability and rotation in space - Idan, Mahmoud Fadhel; Hussein, Osamah Mahmood (Institute of Advanced Engineering and Science, 2025)
The study aimed to create a model of a satellite structure that meets the necessary criteria for stability and rotation in space. The satellite being analyzed has an octagonal shape, with a diameter of 110 cm and a height of 85 cm. A dynamic modeling approach was used to analyze the structural properties, and the finite element method (FEM) was employed for computational analysis. This method allowed for a comprehensive evaluation of stress, displacement, and vibration distribution throughout the structure, providing insight into the behavior of the communications satellite in space. The test model frame consists of plates and bars arranged in an octagonal shape. The analysis utilized the von Mises stress (σvM) criterion to assess the yield strength or brittleness of the chosen material, 7,057 aluminum alloy. The study revealed that the structure demonstrates stability in six different modes but also exhibits deformation due to modifications in the basic arrangement. Additionally, transient fluctuations in the spacecraft's position over a 24-hour cycle result in changes in torque. The structure remains stable within a specified frequency range starting at 150 Hz when subjected to vibration stimuli, and no external instability was detected within this range.